2006
DOI: 10.1098/rsbl.2005.0436
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous processing of abstract categorical information in the ventrolateral prefrontal cortex

Abstract: In various aspects of linguistic analysis and human cognition, some forms of observed variation are ignored in the service of handling more abstract categories. In the absence of training, rhesus discriminate between different types of vocalizations based on the information conveyed as opposed to their acoustic morphologies. We hypothesized that neurons in the ventrolateral prefrontal cortex (vPFC), an area involved in auditory-object processing, might be involved in this spontaneous categorization. To test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 33 publications
4
42
0
Order By: Relevance
“…Abbreviations are the same as in Figure 3. between calls from different categories that have similar semantic meaning. In additional studies, Cohen et al (2006) have shown that there is more information in the responses of single neurons about different calls within the category nonfood than within the category food, but they did not indicate the amount of information about stimuli across categories. Another important point is that categorical representations are nonlinear functions of the acoustics (Nearey, 1997), as we have shown here with the HMM model, so that distinctions between categorical and acoustic representations come down to distinctions between linear and nonlinear representations of acoustic information, which are difficult distinctions to make in the brain, because most representations are nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…Abbreviations are the same as in Figure 3. between calls from different categories that have similar semantic meaning. In additional studies, Cohen et al (2006) have shown that there is more information in the responses of single neurons about different calls within the category nonfood than within the category food, but they did not indicate the amount of information about stimuli across categories. Another important point is that categorical representations are nonlinear functions of the acoustics (Nearey, 1997), as we have shown here with the HMM model, so that distinctions between categorical and acoustic representations come down to distinctions between linear and nonlinear representations of acoustic information, which are difficult distinctions to make in the brain, because most representations are nonlinear.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in macaque monkeys have shown that vocalizations can form discrete categories based on their spectro-temporal acoustic profile . These categories might be generated from acoustic cues and represented in the anterior ventral stream (Rauschecker, 2012) and categorized by the IFC (Cohen et al, 2006Gifford et al, 2005;Russ et al, 2008b). Indeed, recent animal studies have identified neurons in the IFC (see Fig.…”
Section: Origins Of the Ifc Sensitivity To Vocal Intonationsmentioning
confidence: 99%
“…Instead of low-level auditory features, these neurons seem to Single cell activity was usually recorded in BA 45A and BA 9/46v, both located rostrally to BA 8Av below the principal sulcus. Color-coded dots refer to the following studies: (Gifford et al, 2005), Romanski et al, 2005), (Cohen et al, 2007Russ et al, 2008a), (Romanski and Goldman-Rakic, 2002), (Cohen et al, 2006), (Lee et al, 2009;Russ et al, 2008b), (Sugihara et al, 2006), and (Gil-da-Costa et al, 2006) for activity in the vPM. Abbreviations: as arcuate sulcus, cs central sulcus, ipd inferior precentral dimple, ls lateral sulcus, ps principal sulcus, vpm ventral premotor area.…”
Section: Origins Of the Ifc Sensitivity To Vocal Intonationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vPFC is thought to be part of a circuit involved in representing auditory objects (Cohen et al 2004b;Rauschecker 1998;Romanski et al 1999 Romanski et al , 2005. In particular, the vPFC may be part of a circuit that processes socially meaningful signals (Cohen et al 2006;Deacon 1992;Gifford 3rd et al 2005).A fuller and more comprehensive understanding of vocalization processing in the vPFC requires that we understand the acoustic features of the rhesus vocalizations and how these acoustic features relate to neural activity. We first characterized the acoustic structure of rhesus vocalizations by calculating their modulation spectra; the modulation spectrum quantifies the spectral and temporal features of an auditory stimulus as seen in a spectrographic representation.…”
mentioning
confidence: 99%